PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT ASTRA INTERNATIONAL DAIHATSU, TBK CABANG NAROGONG - Agung Bagus Wijayanto; Ahmad Hermanto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
The purpose of this study was to determine the effect of compensation and work discipline on job satisfaction of employees PT. Astra International Daihatsu, Tbk Narogong. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population of all employees of PT. Astra International Daihatsu, Tbk Narogong with 93 employees. The technique used is simple random sampling using Slovin formula obtained a sample of 75 employees. Result compensation and work discipline have a positive and significant effect on job satisfaction of employees of PT. Astra International Daihatsu, Tbk Narogong both partially and simultaneous.